Characterizing Injuries in Maine Logging and Forestry Operations: A Novel Dataset Extracted from Pre-Care Records (2008–2022) - Laura E. Jones; Max Tweedale; Nicole Krupa; Cristina S. Hansen-Ruiz; Paul Jenkins; Erika Scott (Journal of Agromedicine, 2026)

Extrapolation of in vitro effect concentrations to in vivo bioavailable concentrations using PBK modelling in humans for two classes of persistent and mobile compounds: triazoles and triazines - Abishek Laxmanan Ravi Shankar; Jenny Irwan; Max Spaenig; Maxim Carlier; Tanja Hansen; Nicole Zumbülte; Barira Islam; Patrik Lundquist; Richard Svensson; Todd Gouin; Timo Hamers; Sylvia E. Escher (Archives of Toxicology, 2026)
Bottom-up in vitro ADME parameterized PBK models play a vital role in Next Generation Risk Assessment (NGRA), which evaluates the toxicological hazards of compounds through New Approach Methods (NAMs). The ZeroPM project, funded by the EU under Horizon 2020, develops strategies to prioritize persistent (P) and mobile (M) compounds for regulatory measures based on exposure levels and toxicological properties. This study developed a quantitative in vitro to in vivo extrapolation (QIVIVE) approach for two classes of PM compounds – 9 triazines and 16 triazoles. The virtual in vitro distribution model (VIVD) derived free medium benchmark concentration values (EC20 and IR1.5 (mol/L)) from a previously published NAMs testing battery. The VIVD model accounted for partitioning and ionization of PM compounds, while a bottom-up PBK model using in vitro ADME data accurately predicted rat plasma concentrations for tebuconazole and cyromazine. The same assumptions were translated to a human oral-route PBK model. Most triazines/triazoles had in vitro ADME data, where the data gaps were filled using read-across approach. The human PBK model employed forward dosimetry to estimate plasma concentrations from preclinical lowest observed adverse effect levels (LOAELs) or hypothetical exposure data, using surface- and groundwater concentrations as worst-case scenarios. Comparison to QIVIVE data indicates that NAMs-derived values are protective and can serve as basis for human risk assessment or risk-based prioritization.

β-galactosidase from Bifidobacterium bifidum for improved in situ synthesis of GOS-oligomers with prebiotic effects - Jacob Flyvholm Cramer; Karina Hansen Kjaer; Christian Clement Yde; Jesper Wichmann; Henrik Max Jensen; Guus A.M. Kortman; Clementina Dellomonaco; Jacob Ewert (International Dairy Journal, 2025)

Attention, sentiments and emotions towards emerging climate technologies on Twitter - Finn Müller-Hansen; Tim Repke; Chad M. Baum; Elina Brutschin; Max W. Callaghan; Ramit Debnath; William F. Lamb; Sean Low; Sarah Lück; Cameron Roberts; Benjamin K. Sovacool; Jan C. Minx (Global Environmental Change, 2023)

Burden of Disease of Dietary Exposure to Four Chemical Contaminants in Denmark, 2019 - Sofie Theresa Thomsen; Lea S. Jakobsen; Hernan G. Redondo; Malene Outzen; Sisse Fagt; Brecht Devleesschauwer; Max Hansen; Freja A. Fabricius; Sara M. Pires (Exposure and Health, 2022)

Dietary exposure to selected chemical contaminants in fish for the Danish population - Lene Duedahl-Olesen; Tommy L. Cederberg; Tue Christensen; Sisse Fagt; Arvid Fromberg; Kit Granby; Max Hansen; Julie Boberg; Jens J. Sloth; Annette Petersen (Food Additives & Contaminants: Part A, 2020)

No apparent role for T-type Ca2+ channels in renal autoregulation - Rasmus Hassing Frandsen; Max Salomonsson; Pernille B. L. Hansen; Lars J. Jensen; Thomas Hartig Braunstein; Niels-Henrik Holstein-Rathlou; Charlotte Mehlin Sorensen (Pflügers Archiv - European Journal of Physiology, 2016)

Effect of increased intake of fish and mussels on exposure to toxic trace elements in a healthy, middle-aged population - Malene Outzen; Anne Tjønneland; Erik H. Larsen; Max Hansen; Klaus K. Andersen; Jane Christensen; Kim Overvad; Anja Olsen (Food Additives & Contaminants: Part A, 2015)

Integrated seaweed cultivation on an abalone farm in South Africa - Deborah V. Robertson-Andersson; Michelle Potgieter; Joakim Hansen; John J. Bolton; Max Troell; Robert J. Anderson; Christina Halling; Trevor Probyn (Journal of Applied Phycology, 2008)

Dietary elevated sucrose modulation of diesel-induced genotoxicity in the colon and liver of Big Blue rats - Lotte Risom; Peter Mller; Max Hansen; Herman Autrup; Jette Bornholdt; Ulla Vogel; Hkan Wallin; Henrik E. Poulsen; Lars O. Dragsted; Steffen Loft (Archives of Toxicology, 2003)